Teachers' Perceptions of The Material In The Existing English Textbook For Nursing Assistant Students - Ardi Subagiyo; Slamet Setiawan; Oikurema Purwati (Syntax Corporation, 2022)
The use of appropriate material is important in the English teaching and learning process. However, the existing textbooks sometimes may not fulfill the need of teachers and students. In particular, the English textbooks for SMK students are still general for all skill competencies. They do not fulfill the students’ needs relating to their skill competencies. The main aim of this study is to investigate the teacher’s perception of the English textbook. It focusses on the material on existing English textbook that is used by nursing assistant students, its relevance with students’ need, and the English textbook for nursing assistant student should be, from the teachers’ perspective. This study used a qualitative approach consisting of data collection in form of a questionnaire and interviews. 15 teachers are selected to be the participant in this study based on specific criteria. The result confirmed that the using textbook in classroom activities is very important to assist students’ in gaining learning objectives. However. It should be complemented with other resources to match with student’s need. Some suggestion was added to the English textbook should be.